2015
DOI: 10.1007/s12011-015-0449-6
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Melatonin Against Oxidative Stress and Inflammation Induced by Acute Cadmium Exposure in Mice Testis

Abstract: Cadmium (Cd) is widely used in daily life and was recently recognized as a possible source of human toxicity due to its ability to accumulate in organs. Previous studies have shown that Cd exposure may cause testicular toxicity through oxidative stress and an inflammatory effect. Melatonin has been demonstrated to be an effective anti-oxidant and has an anti-inflammatory effect. The aim of the present study was to investigate the toxicological effects of Cd on reproduction in male mice and the potential protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 80 publications
7
59
0
Order By: Relevance
“…SOD is an important antioxidant defense system in cells. The present study found that testicular SOD activity was significantly reduced in the cadmium-treated group, presumably due to oxidative stress, and the findings were consistent with previous studies [37,38]. By contrast, sulforaphane increased the activity of SOD in mouse testis.…”
Section: Discussionsupporting
confidence: 93%
“…SOD is an important antioxidant defense system in cells. The present study found that testicular SOD activity was significantly reduced in the cadmium-treated group, presumably due to oxidative stress, and the findings were consistent with previous studies [37,38]. By contrast, sulforaphane increased the activity of SOD in mouse testis.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the melatonin supplementation of semen extenders increases sperm motility and viability, and decreases ROS levels and lipid peroxidation [80], which improves the sperm quality after the freezing-thawing processes [133]. This antioxidant can protect from testicular injury induced by oxidative stress after cadmium (Cd) exposure [96]. Melatonin helps to protect sperm from ROS induced by cell sorting, a widely used technique for in vitro fertilization or artificial insemination [133].…”
Section: Melatonin Modulates Oxidative Stress On Gametes and In VImentioning
confidence: 99%
“…As the biological roles of melatonin were widely studied, the recognized therapeutical effects and the health benefits of melatonin could cover a broad range. Melatonin could regulate human physiological rhythm, alleviate related disorders like jet lag [2] and insomnia [3], scavenge free radical species [4], enhance the immune system [5], show anti-aging [6] and anti-inflammatory effects [7] and perform anticancer activities [8]. Moreover, melatonin could also exhibit neuroprotective effects [9], facilitate the control of chronic diseases, such as cardiovascular diseases [10], diabetes [11] and obesity [12].…”
Section: Introductionmentioning
confidence: 99%